Having it all. [article].
Women earn less than men because their careers differ. The occupations that may opt for, such as teaching and nursing, are less lucrative than those chosen by men, perhaps because of the long history of putting less value on women's work.
Keywords: Families and work-Periodicals.; Women; Gender equality at work; Women at work